A switchable DNA origami nanochannel for regulating molecular transport at the nanometer scale. Issue 7 (3rd February 2016) - Wang, Dianming; Zhang, Yiyang; Wang, Miao; Dong, Yuanchen; Zhou, Chao; Isbell, Mark Antonin; Yang, Zhongqiang; Liu, Huajie; Liu, Dongsheng
Abstract : A nanochannel with a shutter at one end was built by DNA nanotechnology. Abstract : A nanochannel with a shutter at one end was built by DNA nanotechnology. Using DNA hybridization the shutter could be opened or closed, influencing the transport of materials through the channel. This process was visualized by an enzyme cascade reaction occurring in the structure.